Level of Consumer Satisfaction Towards Brown Rice in Malang District: A Customer Satisfaction Index (CSI) Analysis - Faishal Rafli Ra'if; Bambang Yudi Ariadi; Fithri Mufriantie (Agriecobis : Journal of Agricultural Socioeconomics and Business, 2024)
In general, the current demand for brown rice does not receive the same attention from the public as white rice. So, it is important to further understand consumer behavior related to consuming brown rice because this has an impact on consumer satisfaction and has an impact on the strategies formulated by producers. Thus, this study aims to assess the level of consumer satisfaction with brown rice and evaluate the performance and importance of certain attributes. The variables analyzed include product quality, price, and benefits. This study applied a quantitative approach with Accidental Sampling technique, involving 100 respondents who were analyzed using the Customers Satisfaction Index (CSI) technique. The results of these findings indicate that the product quality variable (Taste) has the highest level of importance and performance, with values of 4.56 and 4.49, respectively. The level of satisfaction of brown rice consumers in Pakis District, Malang Regency, reached 74.53%, which is classified as satisfied (range 60.1% - 80.0%). The suggestions given are that producers need to improve the quality of brown rice in terms of taste, color, and texture, while marketers are advised to utilize social media and creative campaigns to attract young consumers and offer discounts for large purchases to increase customer satisfaction.